Licraside as novel potent FXR agonist for relieving cholestasis: structure-based drug discovery and biological evaluation studies - Xi, Lili; Shi, Axi; Shen, Tiantian; Wang, Guoxu; Wei, Yuhui; Guo, Jingjing (Frontiers in Pharmacology, 2023)
Cholestasis is a common clinical disease caused by a disorder in bile acids (BAs) homeostasis, which promotes its development. The Farnesoid X receptor (FXR) plays a critical role in regulating BAs homeostasis, making it an important target for cholestasis treatment. Although several active FXR agonists have been identified, effective drugs for cholestasis are still lacking. To address this, a molecular docking-based virtual screening method was used to identify potential FXR agonists. A hierarchical screening strategy was employed to improve the accuracy of screening, and six compounds were selected for further evaluation. Dual-luciferase reporter gene assay was used to demonstrate FXR activation by the screened compounds, and their cytotoxicity was then evaluated. Among the compounds, licraside showed the best performance and was selected for in vivo evaluation using an ANIT-induced cholestasis animal model. Results demonstrated that licraside significantly reduced biliary TBA, serum ALT, AST, GGT, ALP, TBIL, and TBA levels. Liver histopathological analysis showed that licraside also had a therapeutic effect on ANIT-induced liver injury. Overall, these findings suggest that licraside is an FXR agonist with potential therapeutic effects on cholestasis. This study provides valuable insights for the development of novel lead compounds from traditional Chinese medicine for cholestasis treatment.